NEW DRAFT OF WATER CODE OF THE REPUBLIC OF KAZAKHSTAN: LEGAL ANALYSIS (Journal of actual problems of jurisprudence, 2024)
For the purposes of implementation of a water-efficient and water-saving state policy, the regulation of water relations over the past decade requires urgent reform. The development of legal and economic science and practice determines the need to include water in economic turnover, thereby stimulating water users to create a closed loop economy. Thus, in the process of enhancement of water legislation, it is required to consider economic, property, environmental and other aspects. Water relations are regulated by both water and civil legislation, and other natural resource legislation. Therefore, the article notes that it is of essence to ensure an optimal ratio of the norms of these branches of legislation. This document provides an assessment of specific sections of the Water Code that is expected to be adopted in Kazakhstan by 2024. The purpose of the analysis is to uncover key issues that arise in the context of legislative water management. The study tries to identify the weaknesses of the proposed draft law from the authors' point of view. Specific proposals are recommended to eliminate legal conflicts, gaps between the norms of land, water and legislation on subsoil and subsoil use of Kazakhstan. Keywords: water, water body, Water Code, legal regulation, water relations.